Efficacy of Sangkareho Leaves Ethanol Extract (Callicarpa longifolia l.) As Anti-Diarrhea - Munifah Wahyuddin (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
Diarrhea is a public health problem in developing countries such as Indonesia, because it still often occurs in the form of Extraordinary Events (KLB), and is accompanied by high mortality, especially in Eastern Indonesia. Based on the results of Riskesdas in 2007, it was shown that diarrheal disease was the main cause of death in infants. This study aims to determine the concentration of how much extract from DaunSangkareho can provide antidiarrheal effects on male mice test animals by looking at the frequency and consistency of stool. 15 mice were used which were divided into 5 groups and each group consisted of 3 mice, the negative control group was given a 1% Na.CMC suspension, groups II, III, and IV were given extracts of 2%, 4%, and 6 respectively. % b / v, as a treatment group. And for group V was given positive control of the loperamid-HCl suspension as a comparison. All groups were injected with English saline solution orally as diarrhea inducers. Evaluation of antidiarrheal effects was carried out by observing the consistency of mouse stools every 1 hour for 10 hours. The results showed that Sangkareho Leaf Extract with a concentration of 2%, 4%, and 6% b / v, had an antidiarrheal effect on the gastric or intestinal mucosa caused by an English saline solution. Sangkareho Leaf Extract at a concentration of 6% b / v has an optimal antidiarrheal effect and is the same as giving Loperamid-HCl suspension as a comparison.